PENGARUH UPAH KERJA DAN INSENTIF TERHADAP PRODUKTIVITAS KARYAWAN PADA PT. INTERYASA MITRA MANDIRI MEDAN - Fransisca Ramayana (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to determine the effect of wages and incentives on employee productivity at PT. Interyasa Mitra Mandiri Medan. This research is a quantitative descriptive study with a questionnaire instrument with a research population of 40 permanent employees, the determination of the sample using a saturated sample so that the research sample is 40 people. Data analysis techniques in the form of validity and reliability tests, classical assumption test, multiple linear regression and hypothesis testing t (partial) and F (simultaneous). The results showed that the tcount coefficient of the work wage variable was 2.246 and the ttable value was 2.022, so the tcount > ttable (2.246 > 2.022) with a significant value < 0.05 (0.031 < 0.05), the tcount coefficient of the incentive variable was 8.384 and the ttable is 2.022 then the value of tcount > ttable (8.384 > 2.022) with a value of sig < 0.05 (0.000 < 0.05). Furthermore, the value of Fcount of work wages and incentives is 28.243 and the value of Ftable is 2.845, so Fcount > Ftable (28.243 > 2.845 with sig value < 0.05 (0.000 < 0.05). The RSquare value is 0.874 or R2 x 100% of 87, 40%, meaning that the independent variables of the study make a major contribution in explaining employee productivity by 87.40% while the remaining 12.60% is influenced by other factors. The conclusion of the study is that work wages have a significant effect on employee productivity, incentives have a significant effect on employee productivity and simultaneously wages and incentives have a significant effect on employee productivity at PT Interyasa Mitra Mandiri Medan.